Pemanfaatan Sampah sebagai Sumber Energi Terbarukan: Paper Review - Lailatul Fajriyah; Yanif Dwi Kuntjoro; Putri Azmi Millatie (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract Indonesia as a developing country faces serious problems related to the increasing volume of waste, especially in big cities, which has an impact on the environment and public health. In this context, this study discusses the waste problem in Indonesia, efforts to reduce the volume of waste, and the potential of waste management as an alternative energy source that supports the 23% new and renewable energy (EBT) mix target by 2025. The results of this study show that the development of Waste Power Plants (PLTsa) is a promising solution, with several PLTsa already in operation and contributing to waste management and energy provision. This process involves technologies such as Landfill Gas Collection, Gasification, and the use of appropriate thermal technologies. However, in order to maximize the potential of the PLTsa, it needs the support of technology updates, investments, and more adequate regulations. The government has an important role in driving this development and supporting waste management as renewable energy. Along with that, public awareness and participation are also important factors in the success of this program. Keywords: Waste, Indonesia, Waste Power Plant, Renewable Energy, Waste Reduction, Environment, Regulation, Government, Community Participation. Abstrak Indonesia sebagai negara berkembang menghadapi masalah serius terkait peningkatan volume sampah, terutama di kota-kota besar, yang berdampak pada lingkungan dan kesehatan masyarakat. Dalam konteks ini, penelitian ini membahas permasalahan sampah di Indonesia, upaya-upaya untuk mengurangi volume sampah, serta potensi pengelolaan sampah sebagai sumber energi alternatif yang mendukung target bauran energi baru dan terbarukan (EBT) 23% pada tahun 2025. Hasil penelitian ini menunjukkan bahwa pengembangan Pembangkit Listrik Tenaga Sampah (PLTsa) menjadi solusi yang menjanjikan, dengan beberapa PLTsa sudah beroperasi dan berkontribusi pada penanganan sampah dan penyediaan energi. Proses ini melibatkan teknologi seperti Landfill Gas Collection, Gasifikasi, dan penggunaan teknologi termal yang sesuai dengan kebutuhan. Namun, untuk memaksimalkan potensi PLTsa, diperlukan dukungan pembaruan teknologi, investasi, dan regulasi yang lebih memadai. Pemerintah memiliki peran penting dalam menggerakkan pengembangan ini dan mendukung pengelolaan sampah sebagai energi terbarukan. Seiring dengan itu, kesadaran dan partisipasi masyarakat juga menjadi faktor penting dalam kesuksesan program ini. Kata Kunci: Sampah, Indonesia, Pembangkit Listrik Tenaga Sampah, Energi Terbarukan, Pengurangan Sampah, Lingkungan, Regulasi, Pemerintah, Partisipasi Masyarakat.